Emotionality and intelligence in the hooded rat as a function of different periods of post-weaning rearing in a "meaningful" environment - Vasiljkovich, Alexandra (Department of Psychology, 2016)
4 groups of Ss ( N = 24 ) were exposed for different lengths of time to a situation where the variable of "meaningfulness" (in terms of contingency of food and water presentation on behaviour) was manipulated. Predicted differences in weight gain and emotionality but not in problem-solving ability were found. Certain shortcomings of the design as well as the inadequacy of testing tools presently available, were discussed as possible confounding factors. It was concluded that the experimental analysis of behaviour framework offered a useful alternative approach in investigating problems of early development.